PEMANFAATAN BIOMASSA BATANG PISANG (Musa paradisiaca) YANG TERIMMOBILKAN PADA ABU BATU BARA SEBAGAI PENGADSORPSI ION LOGAM BESI (Fe) - Saibun Sitorus; Otta Vianus (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract The using of banana stem biomass (Musa paradisiaca) was immobility at ash coal as an adsorb in metal ions iron (Fe) have been researhed. The adsoption capacity determine of metal ions iron (Fe) used Isoterm Langmuir. The analysis of metal ions iron (Fe) by using spectrophotometer UV/Vis and characterization of fungtional group at biomass applies FTIR. The result of this research shows that banana stem biomasa (Musa paradisiacal) was immobility at as coal could adsorb metal ions iron (Fe). The optimum condition was achieved at the pH 5 (5,4196 mg/L), with optimum period of 60 minutes (5,4280 mg/L), proportion mass at 0,5:1 gram (5,5699 mg/L)  and adsorption capacityof ion iron (Fe)  (2,51004 mg/g). Fungtional groups in banana stem biomass (Musa paradisiaca) was immobility at ash coal  as an adsorb in metal ions iron (Fe) be hydroxyl (-OH), carboksyl (-COO-), sylocsan and sylanol Keywords : Biomass, Musa paradisiaca, ash coal, ,adsorption, metal ions iron (Fe)